Uporaba markovskih verig za zasnovo scenarija razvoja kulturne krajine - Gantar, Damjana (Urbani izziv, 2009)
Scenarios used as a tool in the fields of landscape and spatial planning are gaining popularity, as they enable the vivid representation of a probable or the desired future state of a certain area. Scenarios are usually defined trough a process that combines a differing share of intuition and scientific knowledge. The preference of scenarios based on scientific knowledge and defined methods over intuitively prepared scenarios are the evident course of events and the time line and not just the initial and final situation. The article introduces Markov chain method and its use for scenario building. It compares the applicability and reliability of the results of the Markov chain method with a more simple method of linear extrapolation and will shortly present the findings regarding Markov's chain method use for the presentation of future spatial changes and processes.
Keywords: krajinska identiteta; kulturna pokrajina; metodologija; prostorsko planiranje; prostorsko urejanje; spatial planning